Copolymerization and monomer reactivity ratios of 2-(3-mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate with acrylonitrile - Demirelli, K; Coskun, M; Erol, I (Pergamon-Elsevier Science Ltd, 2000)
The free radical copolymerization of 2-3-(mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate (MCHEMA) with acrylonitrile (AN) has been carried out in 1,4-dioxane at 60 degrees C. The copolymers were characterized by infrared, C-13 and H-1 NMR spectroscopic methods. The copolymer compositions were established by elemental analysis. The reactivity ratios of copolymerization were computed by using the Fineman-Ross and Kelen-Tudos methods, and were found to be r(1) = 0.29 +/- 0.002, r(2) = 0.98 +/- 0.003 and r(1) = 0.21 +/- 0.009, r(2) = 0.75 +/- 0.003, respectively (r(2) is reactivity ratios of MCHEMA). The glass transition temperature and thermal decomposition temperature were investigated by DSC-50 and TGA-50 thermobalance, respectively. The solubility parameters and densities of all the copolymers were determined. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: copolymerization; hydroxyethyl methacrylate; substitute cyclobutane; acrylonitrile; reactivity ratios